Integração de modelagem ecofisiológica, análise de componentes principais e linhas de fronteira na parametrização de modelo de qualidade do solo para eucalipto - Jesus, Murilo Figuerêdo Campos de (2024)
Eucalyptus cultivation encompasses an important sector of the Brazilian economy, with Brazil being a world leader in the production of planted forests of this tree. Investments in productivity gains of eucalyptus have been associated with concerns about the relationship between crop management and soil quality in recent years. The present study aimed to propose a new parameterization procedure for soil quality models connected to productivity gains and planted forest sustainability. The scope of this study included sites with eucalyptus cultivation planted and managed by the company Celulose Nipo-Brasileira S.A. (CENIBRA) from 1990 to 2022 from 44 municipalities in Minas Gerais, Brazil. A company's database was used, where data from physical and chemical analyses of soils and the productivity of each plot through the forest inventory from the average annual increment (MAI) were available. The data from 825 soil profiles were divided into two groups: 70% of the data was used to compose the training group in the analyses of the soil quality model parameterization, and the remaining 30% made up the validation group. The frontier line method was used for 29 variables related to the annual relative productivity MAI/MAI 3-PG. The data were subjected to principal component analysis, and the variables were selected to avoid multicollinearity and by the loading values of 0.707, subsequently obtaining the composition of the Soil Quality Index (SQI) and the weights of each selected variable. The variables soil bulk density (Ds), soil organic matter (OM), available water capacity at 180 cm (AWC), and remaining phosphorus (P-rem) presented the higher influence on eucalyptus productivity and, consequently, have more stability due to their intrinsic characteristics to the site and less change on large scales of forest stands. The sampled areas show good soil quality among the analyzed variables, being 85.7 % (Ds), 70.9% (OM), 84.5 % (AWC), and 75.9% (P-rem), within the two better-identified categories. Moreover, 98.2% of the soils presented hihger SQI (0.8 - 1.0). Considering the results of this work, we can prove that the areas managed with eucalyptus by the company have high soil quality, with reduced losses for the variables bulk density, organic matter, available water capacity at 180cm, and remaining phosphorus.